Some features of the practical implementation of criminological characteristics of crimes committed by prisoners during serving a sentence of imprisonment - Карпенко, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article, based on content analysis of criminological characteristics of crimes recorded in the penal institutions of the closed type and characteristics of their investigation in prison conditions, the most problematic issues related to combating the recidivism of re-sentenced were identified. Scientifically reasoned solutions based on existing institutional and legal framework of criminal procedure in Ukraine are presented. Studying statistics showed that the state of crime in the PI reflects both the ordinary phenomena that are characteristic of crime in the whole country (murder, injuries, damage, theft, etc.) and specific criminal activity that is possible only while serving a sentence (refuse to comply with the requirements of prison officials, escape from prison, actions that disrupt the work of penal institutions, etc.), that specifies the nature and peculiarities of the preliminary investigation of crimes among convicts in prison. It follows that in the PI both general forensic techniques measures, which are executed within the entire Ukraine by the forces and methods of the subjects, involved in the criminal procedure activity, and special technique of pre-trial investigation of crimes that are implemented in accordance with the requirements of the CPC (Art. Art. 215, 216) by police, should be carried out. Practice shows that the structure of the crimes committed by prisoners in isolation from the society, is characterized by the relative constancy: most socially dangerous and criminal acts are aimed at the avoidance of punishment (escape, refuse to comply with prison officials, etc.). From this we can conclude that the main motives for committing crimes by persons who are held in penal institutions, are the various contradictions inherent in the nature of criminal penalties, which are objective and mutual "criminal contamination" of prisoners, weakening and break of their social ties, etc. that should be considered during the preliminary investigation of crimes committed by prisoners during serving a sentence of imprisonment. At the same time, the dynamics of crimes in the PI shows that starting from 1996, the number of registered prisoners’ adventures of this kind is falling. Thus, this process demonstrates a direct causality between general and specific crimes, to which belongs the crime in prisons in our country. On the other hand, it is the result of a variety of subjects of criminal procedural activities aimed at strengthening the fight against crime. That is, with proper external and internal efforts of state and public institutions, crime in the PI as a phenomenon of social nature, is a subject of correlation, monitoring, blocking and neutralizing, including forensic means of prevention.